Inhibition of Staphylococcus aureus biofilm formation by gurmarin, a plant-derived cyclic peptide - Chang, Adeline W.; Dowd, Scot E.; Brackee, Gordon; Fralick, Joe A.; Vediyappan, Govindsamy (Frontiers in Cellular and Infection Microbiology, 2022)
Staphylococcus aureus (Sa) is an opportunistic pathogen capable of causing various infections ranging from superficial skin infections to life-threatening severe diseases including pneumonia and sepsis. Sa produces biofilms readily on biotic and abiotic surfaces. Biofilm cells are embedded in a protective polysaccharide matrix and show an innate resistance to antibiotics, disinfectants, and clearance by host defenses. Additionally, biofilms serve as a source for systemic dissemination. Moreover, infections associated with biofilms may result in longer hospitalizations, a need for surgery, and may even result in death. Agents that inhibit the formation of biofilms and virulence without affecting bacterial growth to avoid the development of drug resistance could be useful for therapeutic purposes. In this regard, we identified and purified a small cyclic peptide, gurmarin, from a plant source that inhibited the formation of Sa biofilm under in vitro growth conditions without affecting the viability of the bacterium. The purified peptide showed a predicted molecular size of ~4.2 kDa on SDS-PAGE. Transcriptomic analysis of Sa biofilm treated with peptide showed 161 differentially affected genes at a 2-fold change, and some of them include upregulation of genes involved in oxidoreductases and downregulation of genes involved in transferases and hydrolases. To determine the inhibitory effect of the peptide against Sa biofilm formation and virulence in vivo, we used a rat-implant biofilm model. Sa infected implants with or without peptide were placed under the neck skin of rats for seven days. Implants treated with peptide showed a reduction of CFU and lack of edema and sepsis when compared to that of control animals without peptide. Taken together, gurmarin peptide blocks Sa biofilm formation in vitro and in vivo and can be further developed for therapeutic use.